Clinical Profile and Outcome of Mechanically Ventilated Children in a Pediatric Intensive Care Unit Surabaya - Qorri Aina; Arina Setyaningtyas; Atika Atika (Biomolecular and Health Science Journal, 2020)
Introduction: Ventilator is used as one of the most frequent life-supportive technology in Pediatric Intensive Care Unit (PICU). There are only few studies from Asian Countries, especially Indonesia regarding the use of ventilator in PICU. The aim of this study was to describe the demographic, indications, length of use, complication, and outcome of patients with ventilator in PICU Dr.Soetomo Hospital, Surabaya.Methods: This is a descriptive study. Collecting data was done retrospectively using medical records of patients using ventilator in PICU Dr. Soetomo General Hospital from January-December 2017 . Statistical analysed was performed using Microsoft Excel 2016.Results: 59 patients met the inclusion criteria. Of the 59 patients, 34 (57.63%) were female and 27 (45.76%) were infant (1-12 months). Common indication of ventilator were status epilepticus and shock that happened in 17 (28.81%) patients. 44 (74.58%) patient was using ventilator >48 hours. There are only 4 (6.78%) of 59 patients that happened to had Ventilator Associated Pneumonia (VAP) as a complication of using ventilator. Mortality occurred in 40 (67.80%) patients and mostly happened in female (60%) and infant (50%). Mortality occurred in 10 (90%) of 11 patients with cardiac failure as the indication of ventilator and in 11 (73.33%) patients who used ventilator ≤48 hours.Conclusion: Status epilepticus and shock was the most common reason for ventilation. Incidence of VAP as the complication of ventilator is relatively low. Relatively high mortality found in age group infants, patients with cardiac failure as indication of ventilator and in patient with short duration use of ventilator.